PRODUTIVIDADE E DINÂMICA TERRITORIAL DA BOVINOCULTURA DE CORTE BRASILEIRA - Weslei Maique Oliveira Lopes (2023)
The aim of this study was to analyze the territorial dynamics and productivity of Brazilian beef cattle farming. An analysis of the territorial dynamics of beef cattle farming was conducted to identify the shift in the production's center of mass over the years. Subsequently, a model was developed to evaluate the production factors that influence the productivity of beef cattle farming using data from the 2017 agricultural census. Descriptive basic statistics, systematic literature review, midpoint analysis technique, and Structural Equation Modeling were used to identify and evaluate the factors. The results showed growth and a displacement of beef cattle production, with the main contributors to the displacement at the regional level being the Midwest and North regions. Correlation analyses between the compound annual growth rate (CAGR) of the cattle herd and the CAGR of pastures revealed an inverse correlation in some municipalities. The PLS-SEM model indicates that the productivity of Brazilian beef cattle farming is influenced by factors related to territory, technology, production, and people. The combination of strategies and investments in these areas can boost the productivity of Brazilian beef cattle farming, ensuring the sector's sustainability and meeting the demand of the domestic and international markets. Keywords: Productivity. Territorial Dynamics. Total Factor Productivity. Structural Equation Modeling.